Disclosure transparency and impression management: A textual analysis of board gender diversity disclosures in Canada. (22nd March 2022) - Ben‐Amar, Walid; Bujaki, Merridee; McConomy, Bruce; McIlkenny, Philip
Abstract: This article examines whether firms' board gender diversity disclosures signal transparency, reveal impression management, or both. To disentangle the two disclosure motives further, we also investigate whether the disclosure features of clarity and tone are related to new women director appointments. Based on initial gender diversity disclosures of 506 Toronto Stock Exchange (TSX) publicly traded firms, our results suggest that firms committed to enhancing board diversity provide clearer disclosures and exhibit a higher level of "optimism" to signal their confidence in the positive outcomes of diversity. In contrast, firms reluctant to enhance their diversity policies engage in impression management through obfuscation and show the most "certainty" in their diversity disclosures to indicate no change to the status quo is required. We also find that tone optimism does translate into enhanced diversity practices while certainty is negatively related to subsequent diversity performance. Taken together, our findings are consistent with the assertion that firms employ a combination of signaling and impression management strategies in their disclosures about diversity practices.